Study on crack propagation behaviors of aircraft internal pressure panels with longitudinal cracks - QIN JianBo; WANG Feng; LÜ Pin; HOU Cheng; FAN XueLing (Jixie qiangdu)
Crack growth analysis of aircraft fuselage panels is one of the important tasks of aircraft damage tolerance design. In this paper, the crack growth behavior and residual strength characteristics of the internal pressure panel of the aircraft fuselage with longitudinal cracks were analyzed from two aspects: damage tolerance experiment and finite element simulation. A horizontal self-balancing test device was used to apply internal pressure load to the fuselage panel to analyze the damage tolerance characteristics of the panel. Based on the finite element method, the stress field distribution at the crack tip of the fuselage panel under internal pressure load was simulated. And the analysis results of the equivalent stress intensity factor and crack growth of different crack lengths were calculated based on the fracture mechanics theory. The comparison between the crack growth results and the test results validates the feasibility of the analysis method. This serves a as a valuable reference for conducting damage tolerance analysis on aircraft fuselage panels subjected to internal pressure loads.